Integrated force/motion trajectory design of parallel robots for singularity robustness during contact tasks - ÖZDEMİR, MUSTAFA (My University, 2023)
Parallel robots have an increasing use in industrial and medical applications. Many of these applications require the execution of contact tasks. However, parallel robots possess drive singularities, which act as invisible barriers inside their workspace. In this paper, we develop an integrated force and motion trajectory planning method for removing drive singularities of parallel robots which perform contact tasks. The method is based on satisfaction of a consistency condition at the singularity, which is stated in terms of the generalized velocities, accelerations and contact forces, provided that the derivative of the associated determinant with respect to time does not simultaneously vanish. It is shown that, in the presence of singularity crossing, either the motion or the force trajectory can be arbitrarily chosen while the other is planned to satisfy the necessary conditions.
Keywords: Harita Mühendisliği-Geomatik; Mühendislik ve Teknoloji; Geotechnical Engineering; Engineering and Technology; MÜHENDİSLİK, ÇOK DİSİPLİNLİ; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); ENGINEERING, MULTIDISCIPLINARY; ENGINEERING; Engineering, Computing & Technology (ENG); Genel Mühendislik; Medya Teknolojisi; Mühendislik (çeşitli); Fizik Bilimleri; General Engineering; Media Technology; Engineering (miscellaneous); Physical Sciences; parallel robot; contact task; motion trajectory; force trajectory; drive singularity; singularity removal; INVERSE DYNAMICS; FORCE CONTROL; MANIPULATORS; MOTION; MODEL; parallel robot; contact task; motion trajectory; force trajectory; drive singularity; singularity removal